2009
DOI: 10.1016/j.vetpar.2008.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of a Trichinella pseudospiralis muscle larva secreted serine protease gene

Abstract: Nematode parasites of the genus Trichinella are intracellular and distinct life cycle stages invade intestinal epithelial and skeletal muscle cells. Within the genus, Trichinella spiralis and Trichinella pseudospiralis exhibit species-specific differences with respect to host-parasite complex formation and host immune modulation. Parasite excretory-secretory (ES) proteins play important roles at the host-parasite interface and are thought to underpin these differences in biology. Serine proteases are among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These results indicated that TspSP-1.2 contributes to the larval invasion of host intestinal epithelial cells and could be a potential vaccine candidate against T. spiralis infection [ 9 ]. A similar protein (TppSP-1) from Trichinella pseudospiralis muscle larvae was identified by Cwiklinski et al [ 10 ]. Analysis of the deduced amino acid sequence found that the histidine residue of the catalytic triad in TsSP-1 was replaced with an arginine residue in the TppSP-1.…”
Section: Parasitic Nematode Serine Proteasesmentioning
confidence: 89%
See 1 more Smart Citation
“…These results indicated that TspSP-1.2 contributes to the larval invasion of host intestinal epithelial cells and could be a potential vaccine candidate against T. spiralis infection [ 9 ]. A similar protein (TppSP-1) from Trichinella pseudospiralis muscle larvae was identified by Cwiklinski et al [ 10 ]. Analysis of the deduced amino acid sequence found that the histidine residue of the catalytic triad in TsSP-1 was replaced with an arginine residue in the TppSP-1.…”
Section: Parasitic Nematode Serine Proteasesmentioning
confidence: 89%
“…Analysis of the deduced amino acid sequence found that the histidine residue of the catalytic triad in TsSP-1 was replaced with an arginine residue in the TppSP-1. This could lead to the loss of proteolytic activity, and the role in the T. pseudospiralis -host interaction needs further research [ 10 ]. Trap et al [ 11 ] identified another putative serine protease by screening a library from T. spiralis adult-newborn larvae mixed stage with a radioisotope-labelled DNA probe.…”
Section: Parasitic Nematode Serine Proteasesmentioning
confidence: 99%
“…Several secreted serine proteases have been identified among T . spiralis ES proteins, including the 69 kDa putative serine protease TsSerP (two trypsin-like domains), the 45 kDa serine protease TspSP-1, and a 35.5 kDa serine protease [ 9 , 11 , 16 18 ]. Most of these have strong antigenicity, specific antibodies for them are easily detected experimentally in infected animal sera, and they have one or two trypsin like domains [ 9 , 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In S. carpocapsae, preliminary assays also pointed out the presence of serine proteases in ESPs. This finding led us to search for genes encoding serine proteases during the S. car- Independently of intron number in vertebrate and invertebrate serine protease genes, the ending of a particular intron is commonly conserved six nucleotides before the Ser 195 codon (44). This feature is also conserved in the sc-sp-1 gene.…”
Section: Discussionmentioning
confidence: 99%